Alexis Pauline Gumbs, Undrowned. Lezioni di femminismo Nero dai mammiferi marini (Altre Modernità, 2025)
Alexis Pauline Gumbs, Undrowned. Lezioni di femminismo Nero dai mammiferi marini(Palermo, Timeo, 2023, 190 pp. ISBN 979-1281227088)